Stress-induced translocation of the endoplasmic reticulum chaperone GRP78/BiP and its impact on human disease and therapy - Amy S. Lee (Proceedings of the National Academy of Sciences, 2025)
Since their discoveries in the 1960s as a family of proteins produced by cells in response to stress, molecular chaperones are increasingly recognized as major regulators of cellular homeostasis in health and disease. Among the heat shock protein 70 family, the 78-kDa glucose-regulated protein (GRP78), also referred to as BiP and encoded by the HSPA5 gene, contains a signal peptide targeting it into the endoplasmic reticulum (ER). Through its interaction with the transmembrane ER stress sensors, GRP78 acts as a master regulator of the Unfolded Protein Response (UPR) which allows cells to adapt to stress observed in many human diseases. The discovery that ER stress not only upregulates GRP78 to cope with ER protein quality control but also actively promotes its relocation to other cellular compartments where they vastly expand its functional repertoire beyond the ER represents a paradigm shift. This Perspective describes the origin and linkage of GRP78 to the UPR and the mechanisms whereby ER stress actively promotes export of GRP78 from the ER, as exemplified by its translocation to the cell surface where it acts as a multifaceted receptor and a conduit for drug and viral entry, as well as its translocation into the nucleus, where it assumes the surprising role of a transcriptional regulator whereby reprogramming the cell’s transcriptome. Furthermore, this Perspective addresses how these and other atypical localizations of GRP78 impact human disease, with emphasis on cancer and COVID-19, and the exciting prospect that drugs targeting GRP78 could dually suppress tumorigenesis and viral infections.